Implementasi Asas-Asas Negara Hukum Dalam Kebijakan Perlindungan Anak: Studi Kasus Penanganan Kekerasan Seksual Di Polrestabes - reza kharisma dwi reza (TARUNALAW Journal of Law and Syariah, 2026)
This study aims to analyze the implementation of the principles of the rule of law in child protection policies, with a focus on the handling of sexual violence cases at the Surabaya City Police Headquarters. The principles of the rule of law examined include legal certainty, equality before the law, legality, and the protection of human rights. This study employs a qualitative method with a juridical-empirical approach, analyzing legal norms alongside observations and interviews with law enforcement officers, victim advocates, and relevant social institutions. The results of the study indicate that normatively, the Surabaya City Police Headquarters has attempted to implement the principles of the rule of law through investigative and inquiry procedures in accordance with Polri operational standards and coordination with related institutions. However, in practice, various obstacles are still encountered, including limited human resources and facilities, slow forensic evidence processes, and the influence of social and cultural factors that hinder reporting and law enforcement. The principle of legal certainty has been implemented through precise administrative mechanisms and reporting systems. the need to increase the capacity of police officers through victim-based training, the provision of child-friendly facilities, strengthening coordination between law enforcement and social institutions, and harmonization of laws and regulations between the Child Protection Law and the Law on Sexual Violence Crimes. These efforts are expected to strengthen the implementation of the principles of the rule of law and realize more just, humane, and effective legal protection for child victims of sexual violence in Indonesia.